The mental health of rural older adults: the role of the built environment in Jintang County - Liang, Ping; Wang, Yan; Wang, Tong (Frontiers in Public Health, 2023)
Mental health of the elderly has become one of the major health challenges facing society today, which has attracted wide concern from scholars in urban areas, but neglected the research on rural areas. Therefore, this paper took the rural elderly residents of 11 sample villages in Jintang County, Chengdu City, Sichuan Province, as the research object. After controlling the demographic characteristics of the elderly in rural areas, this paper attempted to explore the effects of the rural built environment on mental health of the elderly. Through field investigation in the sample villages, 515 valid questionnaires were obtained. The results from Binary Logistic Regression Model show that good marital status, physical health, and education level, well-constructed roads and safe neighborhoods had significant positive effects on mental health of rural elderly. Rural older people who prefer to walk, cycle and use public transport have better mental health. And the accessibility to the periodic market, health station, bus station, village committee, supermarket, and the main road is positively correlated with mental health of rural elderly, while the distance from home to the town center and coach terminal has a significant negative impact on the mental health of the rural elderly. The research results provide a theoretical reference for further construction of rural aging environment.